1998
DOI: 10.1097/00001756-199807130-00022
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphins have orexigenic and anxiolytic activities in mice

Abstract: This study was designed to investigate the effects of endomorphin 1 and 2, recently identified mu-opioid receptor selective peptides, on food intake and anxiety in non-food-deprived mice. The intracerebroventricular (i.c.v.) injection of either endomorphin 1 or 2 (0.03-30 nmol) increased food intake in a dose-related manner. A significant increase was observed 20 min after i.c.v. injection of endomorphin 1 or 2 and continued for 4 h. In the elevated plus maze test, the i.c.v. injection of endomorphin 1 (30 nmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 4 publications
1
43
0
Order By: Relevance
“…These results indicate that the Antidepressant effect of endomorphins J Fichna et al effect of endomorphins is mediated, in great part, through central m-opioid receptors. Endomorphin-1 and endomorphin-2 were shown to possess a high affinity and an extreme selectivity for the m-opioid receptors and most of their effects are mediated through the m-binding sites (Champion et al, 1997;Asakawa et al, 1998;Czapla et al, 2000;Fichna et al, 2005). It has also been demonstrated that there is a significant association between the m-opioid receptors and the etiology of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the Antidepressant effect of endomorphins J Fichna et al effect of endomorphins is mediated, in great part, through central m-opioid receptors. Endomorphin-1 and endomorphin-2 were shown to possess a high affinity and an extreme selectivity for the m-opioid receptors and most of their effects are mediated through the m-binding sites (Champion et al, 1997;Asakawa et al, 1998;Czapla et al, 2000;Fichna et al, 2005). It has also been demonstrated that there is a significant association between the m-opioid receptors and the etiology of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…11,12) Intraperitoneally (i.p.) administered soymorphins-5, -6, and -7 at doses of 3-10 mg/kg increased the percentage (%) of time spent in the open arms (Fig.…”
mentioning
confidence: 99%
“…3-30 nmol i.c.v. produced a dose-related increase in food intake (Asakawa et al 1998), and a similar range, 1-30 nmol/kg (i.v. ), of both endomorphins produced a dose-related decrease in systemic arterial pressure (Czapla et al 1998).…”
Section: Figurementioning
confidence: 69%